Public order of Republic of Italy as impediment in application civil effects of marriage nullity sentences in basis of simulation - Rakoczy, Tomasz (Prawo Kanoniczne, 2020)
The Holy See and the Republic of Italy have cooperated in the sphere of marriage in common form of contracting the bound and in application canonical sentences of nullity in Italian civil law. In the time of Lateran Pacts the State acknowledged mentioned sentences in direct and full way. New Accordo from the year 1984 changed that way. From that time, the procedure of application of civil effects has been conditioned from accordance of set of circumstances, inter alia, from “Italian public order”. The simulation (defect of the will) is present in the both legal systems: canon and Italian. Its meaning is different. Claiming marriage in the basis of simulation is limited in Italian civil law. On the one hand, marriage can not be claimed after no later than one year after its contracting. Due to the mentioned condition Italian jurisprudence worked out the concept “extended marriage live” (prolungata convivenza) and corresponding to the three-years period of time. The doctrine of Italian civil law has distinguished apart from marriage understood as legal act (matrimonio-atto) a second category ie. marriage-relation (matrimonio-rapporto), which is the basic element of society and subject of legal protection as key part of public order. On the other hand, simulation done by one part of marriage is excluded as cause of annulment. It means that canonical sentence of nullity of marriage issued in the base of simulation: after long time of spouses’ together live or done by only one spouse can not be applicated in the Italian legal system. It seems to be better to come back to regulation from Lateran Pacts times.